PENGARUH MENYENDAWAKAN BAYI SETELAH DISUSUI DENGAN KEJADIAN REGURGITASI PADA BAYI USIA 0 - 6BULAN - Delima, Mera; Kartina, Nana; Rosya, Ernalinda (Indonesian Journal of Nursing Health Science, 2018)
Nutrients very well in getting the baby is obtained from breast milk. Malnutrition in infants caused by diarrhea, constipation, vomiting (regurgitation), regurgitation is a discharge of milk that had swallowed back baby. The purpose of this study was to determine The effect Of Baby Burping After Feedings With The Incidence Of Regurgitation In Infants Aged 0 - 6 Months at Lubuk Sikaping Pasaman 2017. Methode the riset of Pre Experiment approach. The population in this study are all mothers breastfeed mothers and infants aged 0 - 6 months of Lubuk Sikaping Pasaman, sampling technique is total sampling and instrument used was the observation format. The results showed infants aged 0-6 months in saltpeter appropriate Standard Operating Procedures regurgitation occurs 23.8% of 21 respondents, and in saltpeter not fit the standard operating procedure occurred regurgitation 66.7% from 9 respondent. The conclusion of the research is No Effect After Breastfed Baby burping Regurgitation With Events In Infants Age 0 - 6 Months, with the results of statistical tests chi-square p value = 0.042 (Î± = 0.05). The research cant to applicated in the work environment of nurses by giving information and the mothers are able to apply the appropriate procedures burping action.Â Keywords: Baby, Burping, Regurgitation Instance